Avoiding inaccurate interpretations of rheological measurements for cement-based materials. (December 2015) - Wallevik, Olafur H.; Feys, Dimitri; Wallevik, Jon E.; Khayat, Kamal H.
Abstract: Rheology is a high quality tool to evaluate the effect of variations in constituent materials and mixture proportions on fresh properties of cement-based materials. However, interpreting rheological measurements is relatively complicated, and some pitfalls can lead to wrong conclusions. This paper offers a review of measuring devices and transformation equations used to express rheological parameters in fundamental units. The paper also discusses some of the major issues that can lead to errors during the interpretation of rheological measurements. Although the Bingham model is mostly used for cement-based materials, some non-linearity has been observed, necessitating the selection of an alternative rheological model, which could influence the rheological parameters. Other measurement errors related to thixotropic and structural breakdown, plug flow and particle migration are also demonstrated. The paper also discusses the challenges of using numerical simulations to derive rheological parameters for complicated rheometers or industrial devices, such as a concrete truck.